Nanoparticle Interactions: Mass Cytometry and Single‐Cell RNA‐seq Profiling of the Heterogeneity in Human Peripheral Blood Mononuclear Cells Interacting with Silver Nanoparticles (Small 21/2020). Issue 21 (28th May 2020) - Ha, My Kieu; Kwon, Sook Jin; Choi, Jang‐Sik; Nguyen, Nguyen Thanh; Song, Jaewoo; Lee, Yangsoon; Kim, Young‐Eun; Shin, Incheol; Nam, Jin‐Wu; Yoon, Tae Hyun
Abstract : In article number 1907674, Tae Hyun Yoon and co‐workers report complementary use of single‐cell based mass cytometry and RNA‐seq techniques for the analysis of the heterogeneous interaction between nanoparticles and human immune cells at a single‐cell level, via the identification of various immune cell types, quantification of cell‐associated nanoparticles, and observation of the changes in transcriptomic profiles and signaling protein expressions.